The use of imaging technology in the assessment of the fetal inflammatory response syndrome—imaging of the fetal thymus. (May 2015) - Sciaky‐Tamir, Yael; Hershkovitz, Reli; Mazor, Moshe; Shelef, Ilan; Erez, Offer
Abstract The fetal inflammatory response syndrome (FIRS) describes a state of extensive fetal multi organ involvement during chorioamnionitis, and is associated with grave implications on perinatal outcome. The syndrome has been linked to the preterm parturition syndrome and is associated with inflammation/infection processes in most of the fetal organs. The fetal thymus, a major organ in the developing immune system involutes during severe neonatal disease and has been shown to be smaller in fetuses with FIRS. Various methods for imaging of the fetal thymus and measurement are described. Currently the only method to diagnose FIRS prenatally is through amniocentesis. We suggest that women who are admitted with preterm labor with intact membranes and those with PPROM should have a detailed sonographic examination of the fetal thymus as a surrogate marker of fetal involvement in intrauterine infection/inflammation processes. © 2015 John Wiley & Sons, Ltd.